2000
DOI: 10.1016/s0006-3207(99)00050-6
|View full text |Cite
|
Sign up to set email alerts
|

Viability of piping plover Charadrius melodus metapopulations

Abstract: , "Viability of piping plover Charadrius melodus metapopulations" (2000). USGS AbstractThe metapopulation viability analysis package, vortex, was used to examine viability and recovery objectives for piping plovers Charadrius melodus, an endangered shorebird that breeds in three distinct regions of North America. Baseline models indicate that while Atlantic Coast populations, under current management practices, are at little risk of near-term extinction, Great Plains and Great Lakes populations require 36% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…For example, increasing outflows from upstream dams has a direct negative impact on the growth and survival of plover chicks downstream from those dams, presumably through food limitation and flooding , but the results of this study indicate that the effects of increased densities (potentially food limitation) can have a further effect, decreasing HY and AHY annual survival by as much as 9%. As in many species with relatively high adult survival, plover population dynamics are highly sensitive to changes in adult survival (McGowan and Ryan, 2009;Plissner and Haig, 2000). In a study of the viability of plover populations across their range, Plissner and Haig (2000) found that an increase of <10% in adult survival values would substantially increase the probability of persistence of both the Great Plains and Great Lakes populations of plovers.…”
Section: Conservation Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increasing outflows from upstream dams has a direct negative impact on the growth and survival of plover chicks downstream from those dams, presumably through food limitation and flooding , but the results of this study indicate that the effects of increased densities (potentially food limitation) can have a further effect, decreasing HY and AHY annual survival by as much as 9%. As in many species with relatively high adult survival, plover population dynamics are highly sensitive to changes in adult survival (McGowan and Ryan, 2009;Plissner and Haig, 2000). In a study of the viability of plover populations across their range, Plissner and Haig (2000) found that an increase of <10% in adult survival values would substantially increase the probability of persistence of both the Great Plains and Great Lakes populations of plovers.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…As in many species with relatively high adult survival, plover population dynamics are highly sensitive to changes in adult survival (McGowan and Ryan, 2009;Plissner and Haig, 2000). In a study of the viability of plover populations across their range, Plissner and Haig (2000) found that an increase of <10% in adult survival values would substantially increase the probability of persistence of both the Great Plains and Great Lakes populations of plovers.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Species with low reproductive rates (i.e., few offspring produced per female) and relatively high adult survivorship are highly sensitive to declines in adult survival (Hitchcock and Gratto-Trevor 1997, Plissner and Haig 2000, Sandercock 2003). Adult and juvenile apparent survival estimates can also be used to calculate recruitment thresholds for population maintenance, which can be used to understand current population growth and stability, and evaluate source-sink dynamics (Ricklefs 1973, Page et al 1983, Mullin et al 2010.…”
mentioning
confidence: 99%
“…Sensitivity analyses have found that adult survival often has the highest elasticity value and potentially the greatest impact on population growth rates (Hill and Carter 1991, Hitchcock and Gratto-Trevor 1997, Reed et al 1998, Plissner and Haig 2000, Larson et al 2002, Sandercock 2003. Effective conservation of migratory shorebirds requires reliable estimates of annual survival rates, but estimates are available for ,10% of shorebird species worldwide (Sandercock 2003).…”
mentioning
confidence: 99%